1998
DOI: 10.1034/j.1600-0420.1998.760217.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative features of patients with exfoliation glaucoma and primary open‐angle glaucoma. The AHEPA study

Abstract: ABSTRACT.Purpose: To describe and compare the preoperative characteristics of Greek patients with exfoliation glaucoma (EXG) and primary open-angle glaucoma (POAG). Methods: We prospectively investigated the preoperative features of 100 consecutive patients undergoing filtration surgery for either EXG, or POAG. We compared 74 patients with EXG and 26 with POAG. Results: EXG patients were older (68.2 vs 62.4 years; p∞0.05) and more often from the countryside (73%). Both glaucomas showed a preponderance for male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
6

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 10 publications
1
34
0
6
Order By: Relevance
“…It is also well characterized that ExG has a more aggressive course and that medical treatment fails more commonly and earlier than in POAG. 40 Our demographic data showing shorter history of medical treatment in ExG patients is reflecting the same fact. However, our earlier series of 69 consecutive DS surgeries in POAG and ExG showed that success rates are equally good in both glaucoma types.…”
Section: Discussionmentioning
confidence: 58%
“…It is also well characterized that ExG has a more aggressive course and that medical treatment fails more commonly and earlier than in POAG. 40 Our demographic data showing shorter history of medical treatment in ExG patients is reflecting the same fact. However, our earlier series of 69 consecutive DS surgeries in POAG and ExG showed that success rates are equally good in both glaucoma types.…”
Section: Discussionmentioning
confidence: 58%
“…21 A second study demonstrated that patients with primary open angle glaucoma had a higher prevalence of diabetes than those with PXF, but diabetes is an extremely common disorder and the numbers in that study were small. 22 Conversely, identical fibrils to those seen in PXF have been histologically demonstrated in the basement membranes and extracellular matrices of extraocular orbital tissues, the skin and visceral organs. [4][5][6] Furthermore, PXF has also been associated with an increased risk of vascular disease, which may be due to the presence of PXF fibrils in the walls of blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic vascular alterations in XFS have been studied in the last 2 decades both with epidemiologic [22][23][24][25][26][27][28][29][30] and pathophysiologic methods. [19][20][21] The epidemiologic reports suggest association between XFS and cardiovascular and cerebrovascular diseases, but the relationship was not consistently found.…”
Section: Discussionmentioning
confidence: 99%
“…Association between XFS and cardiovascular and cerebrovascular morbidity has indeed been detected in some studies [22][23][24] ; but in others, such an association was not found. [25][26][27][28] Recently an association between XFS and aorta aneurysm has been proposed. 29 However, this association was not supported by the results of another similar study, 30 despite the fact that both aorta aneurysm and XFS can be explained by elastosis.…”
mentioning
confidence: 99%